LIMITATIONS AND OPPORTUNITIES OF THE IS-LM MODEL ADAPTATION - Rojas Miranda, Antonio (REVISTA PROCESOS DE MERCADO, 2022)
The Austrian School’s resistance to mathematical models and graphic representations has been a handicap in spreading its thinking. The use of the IS-LM and AS/DA models has been extended in universities and business schools, while Austrian thinking needs a separate and specific and sometimes over-intensive analysis in time as it lacks a simplified model. IS-LM model and an Austrian adapted model provide a range of opportunities to explain the Austrian cycle theory and analyze the differences of Austrians with other schools of thought. Keywords: General Aggregative Models; Austrian; Cycles; Monetary Policy.